Prosociality predicts changes in leisure activities during the COVID-19 pandemic - Konishi, Naoki; Kimura, Motohiro; Takeda, Yuji (Frontiers in Psychology, 2024)
Several studies suggest that leisure activities enhance well-being. In line with this perspective, a recent study indicates that augmenting indoor leisure activities to compensate for diminished outdoor pursuits could sustain or enhance well-being during the COVID-19 pandemic. The present study was designed to identify personality traits that predict such behavioral shifts in indoor versus outdoor leisure activities during the pandemic. The present study included 657 participants (Mage = 41.08) and measured 12 personality traits that a previous study reported were associated with health-protective behaviors during COVID-19. Our findings indicate that the rise in indoor leisure activities correlated with prosocial tendencies toward family and friends/acquaintances (but not strangers), self-centered interest, resilience, and Big Five personality traits. Conversely, the decline in outdoor activities was linked solely to prosociality toward family and friends/acquaintances. Further interaction analysis uncovered that prosocial tendencies toward close relations predicted increased indoor activities as an alternative to outdoor engagements. We concluded that prosociality promoted behavioral changes that significantly prevented infections in intimate others, and it could maintain personal well-being during the COVID-19 pandemic by facilitating behavior change.